Managing the development of digital marketplaces in Asia - Villafuerte, James; Yap, Josef; Park, Cyn-Young (Asian Development Bank, 2021)
The coronavirus disease (COVID-19) pandemic is accelerating digital transformation across Asia and the Pacific. Digital platforms have become prominent intermediaries or marketplaces that allow the exchange of goods, services, and information. They are opening new transaction channels while lowering service costs and enhancing market efficiency. This volume explores topics that include trade and e-commerce, fintech payments, the digital divide, promoting competition, the digitalization of work and the role of universal basic income, and international taxation.